Operative margin control with high‐resolution optical microendoscopy for head and neck squamous cell carcinoma. (9th June 2015) - Miles, Brett A.; Patsias, Alexis; Quang, Timothy; Polydorides, Alexandros D.; Richards‐Kortum, Rebecca; Sikora, Andrew G.
Abstract : Objectives/Hypothesis: High‐resolution microendoscopy (HRME) provides real‐time visualization of the mucosal surface in the upper aerodigestive tract. This technology allows noninvasive discrimination of benign and neoplastic epithelium and has potential applications for intraoperative margin detection. Study Design: Single institution, prospective, feasibility trial (phase I) of in vivo optical imaging. Methods: The study was conducted on patients with squamous cell carcinoma of the upper aerodigestive tract. High‐resolution microendoscopy images obtained during surgery were correlated with histopathologic diagnosis to determine the ability of HRME to differentiate between benign and malignant mucosa. Blinded reviewers evaluated HRME images and made determinations of the status of the mucosa. Accuracy, sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and interrater agreement between multiple raters were calculated to determine the accuracy of HRME imaging. Results: The mean accuracy of reviewers in differentiating neoplastic or benign mucosa was 95.1% (95% confidence interval [CI], 94%–96 %). Sensitivity and specificity were 96% (95% CI, 94%–99 %) and 95% (95 % CI, 90%–99 %), respectively. The NPV was 98% (95% CI, 97%–99%), and PPV was 91% (95% CI, 85%–98%). The Fleiss kappa statistic for interrater reliability was 0.81, with a standard error of 0.014 and a 95% CI (0.78–0.84). Conclusion: High‐resolution microendoscopy allows real‐time discrimination between benign and neoplastic mucosa. High levels of sensitivity and specificity can be obtained with this technology when interrogating mucosal surfaces. Despite several technical limitations, HRME shows promise as a technique for intraoperative margin control and platform for molecular imaging technologies. Level of Evidence: 3b. Laryngoscope, 125:2308–2316, 2015